Cultural Barriers to Counseling Help-Seeking Among Chinese High School Students In Surakarta Indonesia: An Etnographic Study (Exploring Trust, Stigma and Negative Attitudes) - Gunawan; Dwi Yuwono Puji Sugiharto; Sugiyo; Sunawan (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
In an attempt to address personal and social problems, help-seeking behavior in counseling may be influenced by cultural values. This study aimed to analyze the barriers to seeking counseling among Chinese students in Surakarta, Central Java, Indonesia. The research method used a qualitative ethnographic research design. The data collection technique was in-depth interviews with 15 Chinese students, 6 school counselors, 2 parents, and 3 Chinese cultural experts. Interview data has been processed and analyzed using NVivo 12. The results of this study found that there were 3 themes of cultural barriers for Chinese students in Surakarta Indonesia, namely distrust of the counselor's competence in solving student problems, negative stigma about students who carry out counseling activities and negative attitudes towards counseling activities that contrary to the family's collective traditional values ​​of Chinese ethnicity Theoretically, recommendations for this study that multicultural counseling and cross-cultural peer group counseling based on Chinese culture need to be developed, while practically, counselors need to improve their professional competence and cross-cultural counseling personality, especially Chinese cultural values. The urgency and benefits of this research are that it provides a theoretical foundation for counselors to develop cross-cultural counseling theory and, practically, offers in-depth information about the cultural barriers faced by ethnic Chinese students in their help-seeking behavior. Keywords: chinese, counseling, help-seeking behaviors